Faktor-Faktor yang Mempengaruhi Motivasi Kinerja Guru di Sma Partiwi 1 Padang - Wati, Erna; Simanungkalit, Egi Wendi; Putri, Vionanda Aliza; Hanoselina, Yulia (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
Teacher performance is very important in improving the quality of children's education. Teacher performance can be improved by understanding the factors that influence performance. The purpose of this study was to describe the factors that influence the performance of teachers at SMA Pertiwi 1 Padang. This type of research is qualitative research with a phenomenological approach. The data collection method was carried out through interview techniques. Data analysis techniques were carried out through the following stages: data compression, data presentation, and drawing conclusions. The results of the study showed that the factors that generally influence teacher performance at SMA Partiwi 1 Padang are: teacher competence, dedication, discipline, work environment, welfare, professional development, and interpersonal relationships. These factors are divided into two main categories, namely internal factors, such as competence, dedication, and discipline, which play an important role in motivating teachers from within, and external factors, such as a conducive work environment and welfare, which support teacher motivation and productivity from outside.